THE THEMES "FOOD" AND "EATING PROCESS" IN WORLD LITERATURE (Conferencea, 2023)
In modern world literature, food discourse is a common theme that reflects the cultural and social values of different societies. It includes various aspects of food, such as its production, preparation, consumption, customs and beliefs associated with it. Through the food image in literature, writers highlight the importance of food in human life, its role in the formation of social and cultural identity, and the interrelationship between food, society, and the environment.